2022
DOI: 10.12928/notion.v4i2.6003
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Communication and Employability Skills: Mismatch Perspectives of Students, Lecturers, and Employers in Sarawak, Malaysia

Abstract: In Malaysia, graduate unemployability is a problem that is often highlighted. Studies have shown that graduates lack soft skills, such as problem solving, English language proficiency, and communication skills, which contribute to the issue of unemployability. However, these studies have not investigated employability skills from all three perspectives of students, lecturers, and employers to understand whether students are developing the necessary skills to be more employable, and whether lecturers are gettin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…According to Yusuf et al (2022), the use of speech acts that are clear and accurate to the meaning can save meeting time and at the same time can meet the speaker's goals (Yusuf et al, 2022). While Sameer ( 2017), looked at the use of speech acts illocution presented by Leech (1983) in the Principles of Politeness through the utterance that spoken by the teacher during the teaching process (Ong et al, 2022). According to him, the act of illocution is treatment of a person's speech intention.…”
Section: Discussionmentioning
confidence: 99%
“…According to Yusuf et al (2022), the use of speech acts that are clear and accurate to the meaning can save meeting time and at the same time can meet the speaker's goals (Yusuf et al, 2022). While Sameer ( 2017), looked at the use of speech acts illocution presented by Leech (1983) in the Principles of Politeness through the utterance that spoken by the teacher during the teaching process (Ong et al, 2022). According to him, the act of illocution is treatment of a person's speech intention.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Italy, Succi and Canovi (2020) found that only 35% of students self-reported their employability skills matched those sought by employers. Given the international focus on employability (see Idkhan et al, 2021; Ong et al, 2022), examining strategies such as embedded soft skills training in community colleges provides valuable insights that are potentially generalizable across postsecondary education and national contexts.…”
Section: Introductionmentioning
confidence: 99%